The Model of Green HRM in Improving Service Quality With OCBE and Organizational Commitment as Mediation In the Hospital of State-Owned Enterprises (Conceptual Framework) - Asep Saifudin Memet; Ahmad Hidayat Sutawidjaya; Sugiyono Sugiyono; Havidz Aima (Business and Entrepreneurial Review, 2020)
Hospitals today are not only socially managed but also as a health service business that considers aspects of service quality and environmental issues. Therefore, hospital human resources must be handled with Green Human Resources Management so that the quality of services becomes better not only from the business, social aspects but also from the environmental aspects. The role of Organizational Civilization Behavior for the Environment (OCBE) and Organizational Commitment is considered important as mediation. For this reason, this research will examine the Green HRM model in improving Service Quality with OCBE and Organizational Commitment as mediation in the Hospital of State-Owned Enterprises. This study answers the research gap of Green HRM research at the organizational level with more specific outcomes. This research also focused on Green HRM in hospital organizations to see its influence on service quality through OCBE and OC, which were rarely examined before. The application of the concept of Healthcare Service Quality (HEALTHQUAL) in the SQ Variable is also to support or deny the conceptual framework for which there is no empirical study when done in hospitals in Indonesia. Through the hypothesis of the research conducted can be in the form of a FrameWork concept as a basis for further research.